2013
DOI: 10.1037/a0034342
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel context of depression in two American Indian tribes.

Abstract: Objective Depression is a major debilitating disease. For American Indians living in tribal reservations, who endure disproportionately high levels of stress and poverty often associated with depression, determining the patterns and correlates is key to appropriate clinical assessment and intervention development. Yet, little attention has been given to the cultural context of correlates for depression, including the influence of family, cultural traditions or practices, or community conditions. Method We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Our DSM-derived estimates of depression seem low given heightened exposure to risk factors and evidence that other indicators of psychological suffering like suicidality are disproportionately high in many Indigenous communities (Indian Health Service 2015). The validity of measures of internalizing symptoms across cultures has been previously critiqued (Nichter 2010), and our finding could be a signal that current operationalization of MDD misaligns with Indigenous expressions of distress (Kaufman et al 2013;O'Nell 1996).…”
Section: Discussionmentioning
confidence: 68%
“…Our DSM-derived estimates of depression seem low given heightened exposure to risk factors and evidence that other indicators of psychological suffering like suicidality are disproportionately high in many Indigenous communities (Indian Health Service 2015). The validity of measures of internalizing symptoms across cultures has been previously critiqued (Nichter 2010), and our finding could be a signal that current operationalization of MDD misaligns with Indigenous expressions of distress (Kaufman et al 2013;O'Nell 1996).…”
Section: Discussionmentioning
confidence: 68%
“…Depression is traditionally treated with a variety of modalities that include a combination of antidepressant medication, psychotherapy, and other somatic therapies (American Psychiatric Association, 2010). Kaufman and colleagues (2013), who analyzed data from a large representative psychiatric epidemiological study among AIs in two reservation communities, found that depression was related to family, cultural, or community dynamics—most likely all three – which has implications for treatment considerations for depression in AI individuals. Treatment interventions that address interpersonal relationships and family dynamics may be effective in treating depression that is related to family factors (Dirmaier et al, 2012; Brakemeir & Frase, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral health disorders in primary care are prevalent and potentially costly to patients and the health care system (Goldman, Wise, & Brody,1998; Greenberg, Fournier, Sisitsky, Pike, & Kessler, 2015; Kaufman, Beals, Croy, Jiang, & Novins, 2013; Kurian, Grannemann, & Trivedi, 2012; Miranda, Hohmann, Attkisson, & Larson, 1994; Ormel et al, 1994), yet these disorders are often under-recognized and, accordingly, untreated (Mulrow et al, 1995; Swartz & Rollman, 2003; Williams, Kerber, Mulrow, Medina, & Aguilar, 1995). Limited evidence indicates that depression is at least as common (if not more common) among AN/AI people than the general US population (Duran et al, 2004).…”
Section: Introductionmentioning
confidence: 99%